Ultralow-energy amorphization of contaminated silicon samples investigated by molecular dynamics - Defoort-Levkov, Grégoire R. N.; Bahm, Alan; Philipp, Patrick (Beilstein Journal of Nanotechnology, 2023)
Ion beam processes related to focused ion beam milling, surface patterning, and secondary ion mass spectrometry require precision and control. Quality and cleanliness of the sample are also crucial factors. Furthermore, several domains of nanotechnology and industry use nanoscaled samples that need to be controlled to an extreme level of precision. To reduce the irradiation-induced damage and to limit the interactions of the ions with the sample, low-energy ion beams are used because of their low implantation depths. Yet, low-energy ion beams come with a variety of challenges. When such low energies are used, the residual gas molecules in the instrument chamber can adsorb on the sample surface and impact the ion beam processes. In this paper we pursue an investigation on the effects of the most common contaminant, water, sputtered by ultralow-energy ion beams, ranging from 50 to 500 eV and covering the full range of incidence angles, using molecular dynamics simulations with the ReaxFF potential. We show that the expected sputtering yield trends are maintained down to the lowest sputtering yields. A region of interest with low damage is obtained for incidence angles around 60° to 75°. We also demonstrate that higher energies induce a larger removal of the water contaminant and, at the same time, induce an increased amorphization, which leads to a trade-off between sample cleanliness and damage.
Keywords: angle dependency; argon; contamination; energy dependency; ion bombardment; low energy; molecular dynamics; silicon; simulations; water